IMPROVING TEACHERS PERFORMANCE AND SKILLS THROUGH TRAINING ON THE UTILIZATION OF LARGE LANGUAGE MODEL TECHNOLOGY - Rengga Prakoso Nugroho; Muhammad Syifaul Qolbi; Khusnul Khuluq; Muhammad Rifky Maulana; Wahyu Dwi Pamungkas (Jurnal Media Akademik (JMA), 2024)
Mastery of technological competence within the TPACK (Technological Pedagogical Content Knowledge) framework is crucial for educators to succeed in increasingly digital learning environments. This article explores the development and implementation of training on using large language models (LLM) for educators, focusing on their ability to integrate this technology into the learning process. While LLMs are controversial, they offer significant potential to support learning, such as content creation, self-directed learning, and student evaluation. However, the effectiveness of using LLMs heavily depends on the clarity of instructions given by the user, often posing a major challenge. This study employs a simplified Action Learning model comprising three stages: design, implementation, and evaluation. During the design phase, a needs analysis revealed participants' low confidence and understanding of AI technology. The training implementation involved registration, material presentation, and hands-on practice with supervision. Evaluation covered three levels of Kirkpatrick's model: reaction, learning, and knowledge transfer. The evaluation results indicated a significant increase in participants' confidence in using AI, though concerns about the impact of AI on students' critical and creative thinking skills remain. The conclusion suggests that the training effectively enhances participants' understanding and skills in utilizing LLMs. It recommends further research involving a broader range of participants and the use of LMS technology for tracking learning outcomes. The training underscores the importance of improving TPACK competence amid disruptive technological advancements